Negative results of bronchoalveolar lavage fluid metagenomic next-generation sequencing in critically ill patients - Ma, Wentao; Zhao, Yangchao; Lu, Xiaoxiao; Zhang, Li; Ma, Xiaoxu; Gao, Jing; Hou, Junna; Liu, Qiuhong; Zhao, Shilong; Yao, Mengying; Xing, Lihua (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: Reports on negative results of metagenomic next-generation sequencing (mNGS) are scarce. We aimed to explore the diagnostic value of negative results in bronchoalveolar lavage fluid (BALF) mNGS and how to deal with the negative results in patients with severe respiratory disease. Methods: A retrospective analysis was performed on patients suspected severe community-acquired pneumonia who were admitted to the respiratory intensive care unit of the First Affiliated Hospital of Zhengzhou University from January 2020 to December 2021. According to the final diagnosis as the reference standard, the negative results of mNGS were divided into a true negative group and a false negative group. For enrolled patients, we recorded their demographic data, imaging results, laboratory results, therapeutic processes, and prognoses. Results: A total of 21 patients were enrolled in this study, including 16 true negative patients and 5 false negative patients. In the true negative group, interstitial lung diseases were the most and neoplastic diseases were following. In addition to mNGS, 9 patients underwent pathological examination, 7 patients were finally diagnosed by medical history, autoantibodies, and point-of-care (POC) ultrasound. 14 patients eventually discontinued antibiotics, 2 patients underwent antibiotic de-escalation, the average interval time of treatment adjustment was 3.56±2.00 days. In the false negative group, the leading missed pathogen was fungi, followed by tuberculosis bacilli. In contrast to 2 patients underwent pathological examination, 3 patients were confirmed by routine microbiological tests. Conclusions: Negative results of BALF mNGS can help to rule out infection, but missed diagnoses may also exist. It should be re-evaluated with other clinical informations. Pathological examination or repeated mNGS may be viable options when the diagnosis cannot be confirmed.